Mediating effects of trust and fairness on commitment and tax compliance behaviour in the special voluntary disclosure program / Raudhah ‘Aqeela Zamiruddin ... [et al.] - Zamiruddin, Raudhah ‘Aqeela; Bujang, Imbarine; Othman, Rani Diana; A. Girau, Emelia (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2024)
Malaysia grapples significant challenges in securing sufficient tax revenue, primarily due to widespread non-compliance and tax evasion. Tax enforcement measures, such as audits and investigations, are crucial in promoting voluntary compliance and combating evasion, especially since the Self-Assessment System (SAS). The government has also emphasized tax education and awareness programs to improve compliance. Despite these efforts, tax-related dilemmas persist, leading to increased penalties and additional taxes. To address this, Special Voluntary Disclosure Programs (SVDP) were introduced, encouraging delinquent taxpayers to disclose unreported income, offering reduced penalties in return. However, participation in this programs remains below expectation, indicating low taxpayers’ commitment to address non-compliance. This study investigates the relationship between taxpayer’s commitment and compliance behavior under SVDP, highlighting the mediating roles of fairness perception and trust in tax authority. Data from 103 respondents, analyzed using Smart PLS, reveals that commitment significantly influences compliance, with fairness perception playing a key mediator. However, trust in authority was found to have a minimal effect. The findings underscore the importance of fairness and trust in shaping taxpayers’ committal compliance behavior while provide substantial contribution and valuable insights for improving future tax strategies.